Corrosion inhibition mechanisms of metal-organic frameworks in ammonia-rich environments - Cao, Jiao-Jiao; Wu, Yu-Meng; Ge, Jin-Long; Yang, Qing-Min; Chen, Zhen-Yu (Frontiers in Chemistry, 2025)
A range of metal-organic framework (MOF)-based composite materials were synthesized and assessed for their corrosion inhibition properties in ammonia-containing aqueous environments. The interaction mechanisms of these materials with copper surfaces were systematically investigated using electrochemical techniques and surface characterization methods. Based on these analyses, a comprehensive mechanistic model was developed to explain the interplay of the observed factors. The results demonstrated that the corrosion inhibition performance of zeolitic imidazolate frameworks (ZIFs), a representative class of MOFs, is significantly influenced by the surrounding environment. Specifically, experimental analysis revealed a competitive interaction between NH3 and the ZIF ligand in complex reactions, leading to structural instability of the ZIFs. This instability compromises the protective layer formed on the copper surface, resulting in a reduction of up to 60% in corrosion inhibition efficiency and, consequently, insufficient long-term durability.